Learning, Unlearning, and Relearning Together : Unmasking Power in a Students as Partners Program using Collaborative Autoethnography. - Alhadad, Sakinah S. J.; Vasco, Daniela; Williams, Jude C.; Dizon, Pauline; Kapnias, Rachel L.; Khan, Saira B.; Payne, Hayley; Simpson, Bronte C.; Warren, Chantelle D. (Student Success v.12 n.2 p.38-50 https://doi.org/10.5204/ssj.1934, 2021)
We interrogated a students as partners (SaP), co-curricular program that focuses on supporting student learning. To center power and equity in SaP, the program was grounded in social design-based experiment methodology. We considered the manifestation of power and equity beyond higher education, to that of broader socio-political contexts. Collaborative autoethnography (CAE) was used to garner a richer understanding of student-staff experiences of the program. Through CAE, power emerged as central to our collective experiences, and a recognition that power asymmetry in students as partners programs is complex and multi-layered. We found that to address power imbalances in these programs requires considered strategies and intentional designs. Further, CAE, in and of itself, can be a powerful way to foster self-awareness, mutual trust, respect, and the acknowledgement of others in student-staff partnerships. We conclude by recommending the importance of deliberate design for equity and power towards consequential learning and transformational change. [Author abstract]